بررسی روش ترسیمی برای حل مدل¬های برنامه¬ریزی خطی تحقیق در عملیات - Yazdanparast, mohammad; Hakimi, Farhad (Farah Research and Scientific Journal, 2025)
Nowadays problem of combining production, less attention has been paid to the objective function of linear programming models in operations research, resulting in wasteful expenditures. By considering linear programming models, these expenditures can be prevented. There are various methods in mathematics to prevent such wastefulness, one of which is the graphical method. This method is crucial for operations research and is a common technique for solving linear programming models, involving optimizing linear objective functions under linear constraints. The graphical method is particularly useful for solving linear programming problems with two variables, while more complex methods like the simplex method are needed for problems with more than two variables. The purpose of conducting this research is to introduce and examine the graphical method in detail among various optimization techniques, aiming to prevent wastefulness and achieve better optimization. After conducting the research, we concluded that this method is recognized as one of the key tools for analysis and information presentation in various scientific disciplines. Its high ability to visually convey complex concepts allows researchers to present their data and results in an understandable manner for the audience. This research is of a library type and draws from multiple credible scientific sources. As a result, the graphical method has been introduced for solving linear programming models in operations research with all the necessary details, making everyday tasks more efficient and maximizing benefits while minimizing costs.